The assessment of learning outcomes and core competencies of inclusive education teachers. A pilot study - Alessandra Romano; Marika Rullo; Rubina Petruccioli (Firenze University Press, 2021)
This paper presents the findings of a pilot study that involved the participants of the Specialization course for support activities, held at the University of Siena for the academic year 2018-2019. The study represents the first phase of broader research that aims to detect the impact of training devices in supporting the construction of a sense of self-efficacy and strengthening the professional identity of inclusive education teachers in training. The results of this exploratory survey highlight which training devices and practices allow to support the strengthening of the sense of individual and collective self-efficacy and how those impact on the development of the professional identity of inclusive education teachers.   La valutazione dei learning outcomes e delle competenze core degli insegnanti di sostegno. Uno studio pilota Il contributo presenta i risultati di uno studio pilota che ha coinvolto i candidati e le candidate del Corso di specializzazione su sostegno tenuto presso l'Università di Siena per l'a.a. 2018-2019. Lo studio rappresenta la prima fase di una ricerca più ampia che ha l'obiettivo di rilevare l'impatto dei dispositivi formativi nel supportare la costruzione del senso di autoefficacia e il rafforzamento dell'identità professionale di insegnanti di sostegno in formazione. I risultati di questa indagine esplorativa evidenziano quali dispositivi e pratiche formative consentono di sostenere il rafforzamento del senso di autoefficacia individuale e collettiva e come questo impatta sullo sviluppo dell'identità professionale degli insegnanti di sostegno.